Singlet oxygen quenching and radical scavenging capacities of structurally-related flavonoids present in Zuccagnia punctata Cav. - Moran Vieyra, Faustino Eduardo (2009)
The singlet oxygen (1O2) quenching and free radical (DPPH+, ABTS and O2 +) scavenging ability of three structurallyrelated flavonoids (7-hydroxyflavanone HF, 2´,4´-dihydroxychalcone DHC and 3,7-dihydroxyflavone DHF) present in the Argentinean native shrub Zuccagnia punctata Cav. were studied in solution by combining electrochemical and kinetic measurements, mass spectroscopy, end-point antioxidant assays and computational calculations. The results showed that the antioxidant properties of these flavonoids depend on several factors, such as their electron- and hydrogen atom donor capacity, the ionization degree of the more acidic group, solvatation effects and electrostatic interactions with the oxidant species. The theoretical calculations for both the gas and solution phases at the B3LYP level of theory for the Osanger reaction field model agreed with the experimental findings, thus supporting the characterization of the antioxidant mechanism of the Z. punctata flavonoids.